RANCANG BANGUN PRAKTIKUM GERAK MENGGELINDING PADA BIDANG MIRING BERBASIS SENSOR ARDUINOMIKRO UNTUK MENENTUKAN KONSTANTA INERSIA - Yopy Mardiansyah; Taufiq Rahman; Luki Hernando; Delia Meldra (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Experiments of rolling motion on an inclined plane in measuring time and speed have used sensors as time triggers on Arduino so that the resulting data is more accurate. However, the design of the tool that has been developed has not been able to respond to objects at higher speeds. The purpose of this study is to optimize the design of the existing inclined plane practicum tool so that it is able to respond to the motion of objects with higher speeds, longer distances, able to display graphs of distance against time, and speed against time in rolling motion to determine the inertia constant. The research method used is to apply an existing tool design with modified sensor updates and Arduino pro micro. The object used as the test object is a solid ball and a hollow ball with variations in the angle of inclination. The percentage of error in the value of the inertia constant is obtained between 4% to 6%.